2017
DOI: 10.1111/ijd.13725
|View full text |Cite
|
Sign up to set email alerts
|

Trichoscopy – a useful tool in the preliminary differential diagnosis of autoimmune bullous diseases

Abstract: Autoimmune bullous diseases present characteristic trichoscopic patterns. Trichoscopy can be regarded as a rapid in-office preliminary diagnostic method in the differential diagnosis of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
4
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(63 citation statements)
references
References 23 publications
(45 reference statements)
9
49
4
1
Order By: Relevance
“…In 2017, our group described trichoscopic features of 26 patients with pemphigus vulgaris and 17 patients with pemphigus foliaceus [ 52 ]. We concluded that the presence of extravasations (20/26, 76.9%), yellow haemorrhagic crusts (19/26, 73.1%), dotted vessels with whitish halo (6/26, 23.1%), circular vessels (6/26, 23.1%), or polymorphic vessels (6/26, 23.1%) can suggest a diagnosis of pemphigus vulgaris [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, our group described trichoscopic features of 26 patients with pemphigus vulgaris and 17 patients with pemphigus foliaceus [ 52 ]. We concluded that the presence of extravasations (20/26, 76.9%), yellow haemorrhagic crusts (19/26, 73.1%), dotted vessels with whitish halo (6/26, 23.1%), circular vessels (6/26, 23.1%), or polymorphic vessels (6/26, 23.1%) can suggest a diagnosis of pemphigus vulgaris [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, our group described trichoscopic features of 26 patients with pemphigus vulgaris and 17 patients with pemphigus foliaceus [ 52 ]. We concluded that the presence of extravasations (20/26, 76.9%), yellow haemorrhagic crusts (19/26, 73.1%), dotted vessels with whitish halo (6/26, 23.1%), circular vessels (6/26, 23.1%), or polymorphic vessels (6/26, 23.1%) can suggest a diagnosis of pemphigus vulgaris [ 52 ]. The presence of dotted vessels, dotted vessels with whitish halo, clustered dotted vessels, dotted vessels forming “string of pearls,” and lace-like vessels correlated positively with PDAI scalp activity score [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Scalp is a common location of autoimmune bullous diseases [1]. We report a case of 52-year old woman presented with erythroderma associated with pruriginous erythema in the scalp.…”
Section: Sirmentioning
confidence: 95%
“…Trichoscopy in a noninvasive tool for assessing scalp dermatosis [1]. They are only few reports on the interest of trichoscopy in pemphigus [1][2][3].…”
Section: Sirmentioning
confidence: 99%
See 1 more Smart Citation